Physicochemical standardization and evaluation of in-vitro antioxidant activity of Aconitum heterophyllum Wall - Prasad S.K.; Kumar R.; Patel D.K.; Sahu A.N.; Hemalatha S. (My University, 2025)
Objective: To evaluate different physicochemical parameters and in-vitro antioxidant activity of Aconitum heterophyllum (A. heterophyllum), having great medicinal value in treatment of diseases associated to nervous system, digestive system, rheumatism, fever and also in case of bacterial, viral and fungal infections. Methods: Various physicochemical parameters such as extractive values, haemolytic activity, foaming index, swelling index, heavy metal analysis and pesticide content as per the guidelines of WHO were included. Determination of starch grains, crude fiber, fluorescence powder drug analysis and preliminary phytochemical analysis of root of A. heterophyllum were also included. Various phytoconstituents such as total phenols, tannins, flavonoids, flavonols, alkaloids and saponins were quantified in the present study. The ethanolic extract was further screened for in-vitro antioxidant activity using different models. Results: The result depicted a higher extractive value in case of aqueous extract which decreased as the polarity decreased. The haemolytic activity of A. heterophyllum was found to be 212.5 units/g of plant material while chlorinated and phosphate pesticides along with heavy metals were found to be within the standard limits of WHO. The quantitative estimations demonstrated the root to be highly rich in alkaloids while phenols, tannins, flavonoids and saponins were found in less quantity. The in-vitro antioxidant study showed a moderate to low activity in all models which may be attributed to low phenolic and flavonoid content. Conclusion: The valuable information provided in the study will ascertain the identity and authenticity of A. heterophyllum and will help in maintaining quality and purity thus, preventing its adulteration. © 2012 Asian Pacific Tropical Biomedical Magazine.